Effect of sequence of insemination after simultaneous thawing of multiple semen straws on conception rate to timed AI in suckled multiparous Nelore cows - Oliveira, L. Z. [UNESP]; Arruda, R.; de Andrade, A. F. C.; Santos, R. M.; Beletti, M. E.; Peres, R.; Martins, J. P. N.; Hossepian de Lima, V. F. M. [UNESP] (Elsevier B.V., 2012)
The objective was to determine the effect of sequence of insemination after simultaneous thawing of multiple 0.5 mL semen straws on conception rate in suckled multiparous Nelore cows. The effect of this thawing procedure on in vitro sperm characteristics was also evaluated. All cows (N = 944) received the same timed AI protocol. Ten straws (0.5 mL) of frozen semen from the same batch were simultaneously thawed at 36 degrees C, for a minimum of 30 sec. One straw per cow was used for timed AI. Frozen semen from three Angus bulls was used. Timed AI records included sequence of insemination (first to tenth) and time of semen removal from thawing bath. For laboratory analyses, the same semen batches used in the field experiment were evaluated. Ten frozen straws from the same batch were thawed simultaneously in a thawing unit identical to that used in the field experiment. The following sperm characteristics were analyzed: sperm motility parameters, sperm thermal resistance, plasma and acrosomal membrane integrity, lipid peroxidation, chromatin structure, and sperm morphometry. Based on logistic regression, there were no significant effects of breeding group, body condition score, AI technician, and sire on conception rate, but there was an interaction between sire and straw group (P = 0.002). Semen from only one bull had decreased (P < 0.05) field fertility for the group of straws associated with the longest interval from thawing to AI. However, the results of the laboratory experiment were unable to explain the findings of the field experiment. Sperm width:length ratio of morphometric analysis was the single sperm characteristic with a significant interaction between sire and straw group (P = 0.02). It was concluded that sequence of insemination after simultaneous thawing of 10 semen straws can differently affect conception rates at timed AI, depending on the sire used. Nevertheless, the effects of this thawing environment on in vitro sperm characteristics, remain to be further investigated. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Conception rate; Semen characteristics; Simultaneous semen thawing; Timed AI